Kemampuan Ekstrak Kulit Buah Nanas (Ananas Comosus L. Merr) Dalam Mematikan Jentik Nyamuk Culex sp - Marlita Pasinggi; Erlani Erlani; Haderiah Haderiah (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2022)
ABSTRACTCulex sp mosquitoes are known as a type of mosquito vector that can transmit filariasis. Filariasis (elephantiasis) is a disease caused by filarial worms. Control to reduce mosquitoes so far is still focused on chemical control which has a negative impact on the environment, it is necessary to develop the use of pesticides that are environmentally friendly and easily biodegradable.The purpose of this study was to determine the ability of pineapple peel extract to kill Culex sp. This type of research is experimental research. The sample in this study was 20 Culex sp larvae per treatment, so the total larvae used were 300 larvae which would be exposed to pineapple peel extract with concentrations of 1%, 2%, 3% and 4%, whose mortality was calculated every 60 minutes for 3 hours, with 3 repetitions.The results showed that pineapple peel extract at a concentration of 1% was able to kill Culex sp larvae with a mortality percentage of 25%, a concentration of 2% with a mortality percentage of 30%, a concentration of 3% with a mortality percentage of 35%, while at a concentration of 4% it was able to kill 12 larvae. which is the highest percentage of deaths with a mortality percentage of 60%.The conclusion of this study was that pineapple peel extract was only able to kill Culex sp larvae up to 60% so it was not said to be effectivebecause it had not killed larvae up to 80%.